Discovery of New Phases of Bismuth Oxyselenide Semiconductor Bi2OSe2 by Global Structure Search Approach. Issue 6 (28th April 2021) - Wang, Xueting; Zhao, Xingang; Wang, Xinjiang; Li, Hongdong; He, Xin; Zhang, Lijun
Abstract: Bi2 O2 X and Bi2 OX2 (X = S, Se, and Te) have shown potential for thermoelectric, optoelectronic, etc. applications. The ground‐state structures of Bi2 O2 X have been determined experimentally (in space group I 4/ mmm ). However, for Bi2 OX2, only Bi2 OS2 has been synthesized in the experiment (in space group P 4/ nmm ). In previous theoretical studies, the crystal structures of Bi2 OSe2 and Bi2 OTe2 are assumed the same as that of Bi2 OS2 . Whether they can be experimentally synthesized remains an open question. Here, a swarm intelligence‐based structural prediction is employed in combination with first‐principles calculations to predict the crystal structures of Bi2 OSe2 . Three thermodynamically stable low‐energy phases ( P 21 / m, P 4/ nmm, and P 21 / m ′) are identified. Importantly, the newly reported P 21 / m phase, instead of the previously assumed P 4/ mmm phase, has the lowest energy. The P 21 / m ‐Bi2 OSe2 shows marginal stability with respect to decomposition into binary compounds Bi2 O3 and Bi2 Se3 . The predicted phases of Bi2 OSe2 have bandgaps of 0.67–1.19 eV and comparable small electron and hole carrier effective mass (less than 0.65 m0 ). The different phase stability between Bi2 OSe2 and Bi2 OS2 are explained in terms of different Bi─S and Bi─Se covalent bonding characters. Our work provides theoretical guidance for discovering new phases of Bi2 OSe2 and an in‐depth understanding of the structure‐property relationship of Bi─O─S/Se system. Abstract : The ground‐state structures of Bi2 O2 X (X = S, Se, Te) have been determined experimentally, whereas only Bi2 OS2 has been synthesized for the Bi2 OX2 system. Here, a swarm intelligence‐based structural prediction combined with first‐principles calculations is employed to predict the crystal structures of Bi2 OSe2 . Bi2 OSe2 with P 21 / m symmetry is newly predicted, which shows marginal stability, moderate bandgap, and small carrier effective mass.